Microstructure and mechanical properties of Mg–Li–Al based alloy with yttrium addition. (July 2014) - Xu, T. C.; Peng, X. D.; Jiang, J. W.; Zhang, X.; Wei, G. B.
<x content-type="archive" xml:space="preserve">Abstract</x> The Mg–11Li–3Al–xY (LA113–xY, x = 0, 2·0; mass fraction, %) alloys were designed and prepared using a vacuum induction furnace by argon atmosphere, then processed by hot extrusion. The results show that, as yttrium (Y) is added, the LA113–2Y alloy mainly consists of β-Li, LiMgAl2 and Al2Y phases. The fine, granular and dispersed Al2Y phase is favoured for refining matrix crystals and optimising internal microstructure of the alloy. The microstructures of the investigated alloys are crushed into smaller phases, and obviously refined after hot extrusion process. As Y is added, the strength of the alloy also improves by the refining effect and the Al2Y phase. Specifically, the extruded LA113–2Y alloy exhibits a favourable combination of strength and ductility, with yield strength of 227·06 MPa, ultimate tensile strength of 239·65 MPa and elongation of 20·71%.